Land use practices and their implications on soil macro-fauna in Maasai Mara ecosystem - Nyawira Muchane, Mary; Karanja, Daniel; Mwangi Wambugu, Geoffrey; Mwangi Mutahi, Joseph; Masiga, Clet Wandui; Mugoya, Charles; Muchai, Muchane (International Journal of Biodiversity and Conservation, 2012)
The composition, abundance, diversity and species richness of soil macro-fauna communities were assessed in four major land use types present within protected and agricultural landscapes in Maasai Mara savannah ecosystem (MME), Kenya. The four land uses were: natural grassland; woodland, inside and outside protected area; maize mono-cropping and maize-bean intercropping systems in adjacent agricultural farms. Sampling of soil macro-fauna was carried out in November, 2009 (short rain), April 2010 (wet rainy season) and September 2010 (dry season). Hand sorting of soil taken from 25 × 25 × 30 cm monoliths was used to extract all soil macro fauna greater than 2 mm body length. A total of 3,658 individuals comprising of 128 species mainly belonging to Phylum Arthropoda distributed across 3 classes and 13 orders, and Phylum Annelida with one order were collected across the four different land use systems. Termites and ants, and to a lesser extent coleopteran and earthworms were the most abundant groups. Significant effects of land use on macro-fauna abundance and species richness in all cases (p<0.001) were observed. There were significant interaction between Season*Region*Land use (p<0.01), Region*Land use (p<0.05) and Region*Protection*Land use (p<0.02). Grassland and woodland had the highest density (1351.61 vs. 2852.47 individual m-2) of total macro-fauna, whilst the lowest density occurred in agricultural land (205.48 individual m-2). Agriculture altered macro-fauna communities by declining individuals from Order Coleoptera, Hymenoptera and isoptera by > 50% and eliminating some Orders/Species. Human related disturbances outside protected area network declined macro-fauna density in grassland and woodland in dry region (65.07 vs. 39.74%) but increased the density by 107 vs. 340% in wet region. The study highlights the important effect of agriculture on macro-fauna communities and the need for conservation alternatives in unprotected areas. This study supports conservation of biodiversity beyond protected area network.
Keywords: Macro-fauna; Grassland; Woodland; Agriculture; Maasai Mara; Land use